The Impact of Using Learning Video Media Animaker in Social Studies Learning Outcomes: (Quasi Experiment Study for class VII. 3 and VII 4 at SMP N 1 Cikarang Selatan) - Teguh Putra Socrates Socrates; Kokom Komalasari; Wildan Insan Fauzi (Institut Agama Islam Negeri Jember, 2022)
This research is motivated by the increasingly uncertain pandemic Covid-19 situation and has yet to show when it will end. Learning during the pandemic is carried out using the Distance Learning (PJJ) system using limited media. Learning could be carried out face-to-face but returned online due to the increasing number of Covid-19 cases. One of the problems teachers face during online learning is low learning outcomes, especially in social studies subjects. The value of learning outcomes can be increased continuously during the learning process, one of which is utilizing and maximizing learning media. This study aimed to determine whether or not the use of Animaker-based instructional video media on social studies learning outcomes for seventh-grade students of SMP N 1 Cikarang Selatan. This study uses a quasi-experimental quantitative approach with a non-equivalent control group design—data collection techniques used learning outcomes tests and questionnaires distributed to the research sample. The sample in this study is class VII.3 as the experimental class and VII.4 as the control class. The analytical technique used is hypothesis testing with the Wilcoxon test technique or the Mann-Whitney test, using statistical tests assisted by IBM SPSS Statistics Version 25. The results of processing and testing research data show differences that at least increase the learning outcomes of experimental class students after the treatment is applied. , with an Asymp. Sig. (2-tailed) value of 0.000 < 0.05. These results align with the questionnaire data on student responses to the use of Animaker-based learning video media, which received positive acceptance as a medium in social studies learning with a percentage of 81%.